Subsistence, regional planning and the cultural carrying capacity of First Nations in Alberta, Canada. Issue 4 (April 2019) - Natcher, David C
Abstract : This paper presents the results of the Lower Peace River Environmental Livelihoods Assessment that was carried out by the Lubicon Lake, Beaver, Tallcree and Little Red River Cree First Nations of Alberta Canada. Based on a census of 879 First Nation households (94% of all on-reserve households) results indicate that 49% (427/879) of First Nation households harvested traditional foods during the 2016 survey period. Traditional foods include large and small mammals, fish and birds that are acquired through hunting, fishing and gathering activities. The total amount of traditional foods harvested was estimated to be 246, 090 kg. Considerable variability between household harvesting levels was found, with 20% (N=174) of households harvesting 90% of the total food harvest (222, 334 kg) with an even smaller number of super-harvesting households producing the majority of their Nation's traditional food supply. The primary constraints that limited household harvesting were time limitations associated with employment, financial costs and limited knowledge and interest to participate in subsistence activities. These social-economic conditions may precipitate a cultural tipping point where changes in First Nation livelihoods bring about fundamental change in norms, values and place-based identity. Using the concept of cultural carrying capacity, this paper shows how First Nation governments are collaborating with the Alberta provincial government to develop a regional land use plan that protects the livelihoods and land-based values of First nation members.